Lugo Press during Galician Statute of Autonomy (1936) - Abejón Mendoza, Paloma (2011)
If Galicia is nowadays considered a historical community, along with Catalonia and Basque Country, is because Galicia approved, in referendum, its first Statute of Autonomy in 1936. That first Statutory text was presented by Castelao and other intellectuals and politicians to the President of Spain on July the 15th 1936. However the burst of Spanish Civil War, just three days later, prevented the discussions in Court and it was not until 43 years later (1979) when Galicia made its autonomist dream come true. The purpose of this research is to analyze how this autonomist phenomenon was approached by the existingpublications in the province of Lugo during the Second Spanish Republic.